2022
DOI: 10.1007/s00417-022-05569-x
|View full text |Cite|
|
Sign up to set email alerts
|

Predictability of success and open conjunctival revision rates in the subsequent eye after XEN45 Gel Stent implantation according to lens status

Abstract: Purpose To determine the predictability of success and the risk of open conjunctival revision in the subsequent eye after XEN45 Gel Stent implantation according to lens status. Methods This was a retrospective single-centre study involving 132 eyes of 66 participants who had undergone intraocular pressure (IOP)-lowering XEN45 Gel Stent implantation, either as a standalone procedure in phakic and pseudophakic eyes or in combination with phacoemulsification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Similar trends have been reported on trabeculectomy, 1 deep sclerectomy 2 as well as on XEN45 Gel Stent implantation 3,7 . Considering surgery targeting the iridocorneal angle primarily, Rosentreter et al made comparable observations on combined cataract surgery with trabecular aspiration 4 .…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Similar trends have been reported on trabeculectomy, 1 deep sclerectomy 2 as well as on XEN45 Gel Stent implantation 3,7 . Considering surgery targeting the iridocorneal angle primarily, Rosentreter et al made comparable observations on combined cataract surgery with trabecular aspiration 4 .…”
Section: Discussionmentioning
confidence: 52%
“…Similar trends have been reported on trabeculectomy, 1 deep sclerectomy 2 as well as on XEN45 Gel Stent implantation. 3,7 Considering surgery targeting the iridocorneal angle primarily, Rosentreter et al made comparable observations on combined cataract surgery with trabecular aspiration. 4 In addition, we recently provided data on a considerable predictive association between successful ab-interno trabeculectomy via Trabectome in first and subsequent eyes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[124][125][126][127] Reitsamer et al 128,129 did not find a difference if XEN was performed as a standalone or combined with cataract surgery in 2 studies with a 2 and 3-year follow-up. Kiessling et al 130 found a 60% risk for revision surgery in standalone XEN in phakic eyes, and Lewczuk et al 131 showed a 24% need for subsequent glaucoma surgery. Torbey et al 132 found complete success at 3 years to be a predictor for success at 5 years and needling was associated with failure.…”
Section: Outcome and Safetymentioning
confidence: 99%